1972
DOI: 10.1039/p19720002584
|View full text |Cite
|
Sign up to set email alerts
|

The nonadrides. Part VI. Dimerisation of the C9 unit in vivo and in vitro

Abstract: But-I -enyl(methyl)maleic anhydride (4) has been synthesised and shown to act as an efficient (55% incorporation) precursor of the cyclononadienes, glauconic and glaucanic acids, in Penicillium purpurogenum. Base-catalysed dimerisation of compound (4) yields 5% of an epimer of glaucanic acid.IN Part V evidence, based on feeding of labelled acetate, succinate, glucose, and n-butyl(methy1)maleic anhydride, was presented supporting the hypothesis that a key step in the biosynthesis of glaucanic acid (1) was the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 0 publications
1
26
0
Order By: Relevance
“…11 Later, a biomimetic synthesis of 12-epi-glaucanic acid was achieved by Sutherland via treatment of a DMF solution of anhydride 5 with triethylamine to afford 8. [12][13][14] Although the dimerization product 8 was obtained in only a 4% yield, the outcome nonetheless provided further evidence supporting a dimerization biosynthetic pathway for the nonadrides.…”
Section: Discovery and Classification Of The Phomoidridesmentioning
confidence: 81%
“…11 Later, a biomimetic synthesis of 12-epi-glaucanic acid was achieved by Sutherland via treatment of a DMF solution of anhydride 5 with triethylamine to afford 8. [12][13][14] Although the dimerization product 8 was obtained in only a 4% yield, the outcome nonetheless provided further evidence supporting a dimerization biosynthetic pathway for the nonadrides.…”
Section: Discovery and Classification Of The Phomoidridesmentioning
confidence: 81%
“…Recreation of this dimerisation step in vitro is an attractive strategy for the total synthesis of nonadrides. Early work by Sutherland showed that treatment of 12 with Et3N in DMF could promote cyclisation giving iso-glaucanic acid 13 in 4% isolated yield, 27 and this work was further developed by Baldwin using Et3N and MgCl2 in DMSO which gave 13 along with further products. 28 Sulikowski tethered the two methylmaleic anhydride moieties together to enhance the efficiency of ring formation.…”
Section: Scheme 1 Proposed Biosynthesis Of Nonadrides and A Biomimetimentioning
confidence: 99%
“…This may be attributed, in part, to an early report from Sutherland which indicated that such compounds are unstable. 27 Pursuing an interest in the biosynthesis of maleidride natural products with fungicidal activities, herein we describe recent studies on the total syntheses of fungal dienoic acids tricladic acids A, B and C as well as the reported structure of waquafranone B isolated from Wicklowia aquatica and analogues of the exo-diene monomer 10 required for dimerisation studies. 31,32…”
Section: Scheme 1 Proposed Biosynthesis Of Nonadrides and A Biomimetimentioning
confidence: 99%
See 1 more Smart Citation
“…All three metabolites, 1 , 3 and 4 , were hypothesised to be biosynthesised via alternative dimerisation modes of a C 9 /C 10 -maleic acid precursor 5 and/or 6 , and evidence for this was obtained by feeding studies with radiolabelled 6 . 9 Many more nonadride metabolites have since been reported, e.g. heveadride 7 , 10 an isomer of 1 , and others which are expected to be biosynthesised through dimerisation of differently substituted maleic anhydride units, including scytalidin 8 , 11 and castaneolide 9 .…”
mentioning
confidence: 99%